PENGARUH RETRIBUSI TERMINAL DAN RETRIBUSI PELAYANAN PASAR TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KARANGANYAR - Tri Widyatmoko, Siti Nurlaela & Suhendro (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Locally-generated revenue is all revenue from regions originating from region itself. Among the locally-generated revenue sources are terminal retribution and market service retribution. This study aims to determine the effect of terminal retribution and market service retribution on local revenue in Karanganyar Regency. The population of this study is all the monthly financial report data from the Karanganyar District Regional Finance Agency in 2013-2017 (5 years). The sample used in this study were 60 samples. The sampling technique uses purposive sampling method. Hypothesis testing of this study using multiple linear regression test. The results showed that: 1) Terminal levies did not have an influence on the original regional income of Karanganyar Regency, 2) Market service levies had a positive effect on the original regional income of Karanganyar Regency. Keywords: Locally-generated revenue, terminal retribution, market service retribution